Inhibitory effect of high-strength ammonia nitrogen on bio-treatment of landfill leachate using EGSB reactor under mesophilic and atmospheric conditions - Liu, Jianyong; Luo, Jinghuan; Zhou, Jizhi; Liu, Qiang; Qian, Guangren; Xu, Zhi Ping (Bioresource technology, 2012)
The inhibitory effect of high-strength NH3-N on anaerobic biodegradation of landfill leachates in an EGSB bioreactor has been investigated. The research compared start-up performance of the reactor treating the landfill leachate with NH3-N in 242–1200mg/l to that treating the compost leachate with NH3-N in 38–410mg/l. The observations showed that the performance of the reactor treating the landfill leachate was only marginally worse than that treating the compost leachate at the mesophilic temperature when NH3-N concentration was under 1500mg/l. We also noted that NH3-N at the concentration of 1500–3000mg/l inhibited the biodegradation. The comparative biodegradation performance at the mesophilic and atmospheric temperature demonstrated that the maximal OLR of atmospheric digestion was only reduced to 44kgCOD/m3d. These findings indicate that landfill leachates with NH3-N less than 1500mg/l could be efficiently treated in the EGSB bioreactor even under the atmospheric condition with methane generated.